Revealing the beneficial effects of a dairy infant formula on the gut microbiota of early childhood children with autistic spectrum disorder using static and SHIME® fermentation models - Gomes de Oliveira, Louise Iara; Clementino, Jéssika Rodrigues; Salgaço, Mateus Kawata [UNESP]; de Oliveira, Sônia Paula Alexandrino; dos Santos Lima, Marcos; Mesa, Victoria; de Souza, Evandro Leite; Vinderola, Celso Gabriel; Magnani, Marciane; Sivieri, Katia [UNESP] (Royal Society of Chemistry (RSC), 2023)
This study evaluated the impact of the Milnutri Profutura® (MNP) dairy infant formula on the gut microbiota of early childhood children (three to five years) with Autistic Spectrum Disorder (ASD) using static fermentation (time zero, 24, and 48 h) and the Simulator of the Human Intestinal Microbiol Ecosystem (SHIME®) (time zero, 72 h, and 7 days). The relative abundance of selected intestinal bacterial groups, pH values, organic acids, and sugars were verified at time zero, 24, and 48 h using flow cytometry and measurements. In addition, the diversity and changes in the gut microbiota, and the amounts of acetic, butyric, and propionic acids and ammonium ions (NH4+) in fermentation using the SHIME® were measured at time zero, 72 h, and 7 days. MNP increased Lactobacillus/Enterococcus and Bifidobacterium populations and decreased Bacteroides/Prevotella, Clostridium histolyticum and Eubacterium rectale/Clostridium coccoides populations (p < 0.05) at 24 and 48 h of static fermentation, showing a positive prebiotic activity score (65.18 ± 0.07). The pH, fructose and glucose decreased, while lactic, butyric, and propionic acids increased (p < 0.05) at 48 h of static fermentation. MNP increased (p < 0.05) the Firmicutes phylum during the fermentation in SHIME®. MNP decreased the diversity at 72 h of fermentation, mostly by the increase (p < 0.05) in the Lactobacillus genus. Microbial groups considered harmful such as Lachnospiraceae, Negativicoccus, and Lachnoclostridium were inhibited after administration with MNP. Propionic and butyric acids increased at 72 h and NH4+ decreased (p < 0.05) at the end of fermentation with MNP. The results indicate MNP as an infant formula which may benefit the gut microbiota of children with ASD.